ЩОДО УДОСКОНАЛЕННЯ ДІЮЧИХ НОРМАТИВНИХ ДОКУМЕНТІВ ДЛЯ РОЗРАХУНКУ ЗГИНАЛЬНИХ ДЕРЕВ’ЯНИХ ЕЛЕМЕНТІВ ТА КОНСТРУКЦІЙ (Collection of scientific works «Modern structures of metal and wood», 2023)
The  most  common  use  of  wood  in  construction  is  for  bending  elements.  The calculation  of  bending  members  made  of  glued  laminated  timber  requires  the  use  of  the  section modulus of this member and the calculated values of the bending strength of the timber. The design bending strength of wood is determined based on the characteristic values obtained from the laws of elastic material under load. However, this statement completely contradicts the anisotropy of wood in  its  tensile  and  compressive  behavior.  If  it  is  known  that  wood  works  90-95%  to  failure  in longitudinal tension, it is then it can be assumed that it is elastic at all. However, in longitudinal deformation, there is non-linear behavior with increasing elastic and plastic strains. Furthermore, the  longitudinal  tensile  strength  of  wood  is  almost  twice  that  of  longitudinal  compression.  Therefore, even if the relative deformations in the wood are the same different compressive and tensile stresses arise in the bending element, i.e.  Many authors who have carried out experimental and theoretical studies on the performance of timber beams have pointed out that the neutral force line in the cross-section of the element in direct  transverse  bending,  with  increasing  levels  of  single  load,  shifts  towards  the  tensile  zone. Therefore, using the moment of resistance of the cross section in the wooden element to determine the section modulus is incorrect. The moment of resistance of a section of a timber member is only determined if the centre of gravity of the section coincides with the centre of force line.  Usually, the failure of long wooden beams in transverse bending usually occurs due to the fracture of the most stressed outer layers of wood in the of the tensile area and is brittle in nature. It is on such elements that the the temporary bending strength.  It is on such elements that the bending strength is crucial. However, the values of m f , usually determined in the outermost wood layers of the tensile zone, based on the  condition, only reach values of 70-75% of the longitudinal tensile strength of wood. It is not possible to determine the tensile strength of wood at this stress level.  Therefore,  the  results  of  determining  the  bending  strength  of  wood  using  the  moment  of resistance  of  the  cross-section  of  a  timber  element  determined  in  the  limiting  condition  are erroneous due to the impossibility of establishing W  values.